Importancia de las micro y pequeñas empresas de Loreto en la generación de empleo periodo 2018 – 2022 - Salcedo Ramirez, Ricardo Bladimir (2024)
Micro, small and medium-sized businesses have become the main job generators in Peru and the world, and Loreto is no exception, a behavior that is analyzed in this research. The objective of this master thesis is to analyze the importance of micro and small businesses in Loreto in generating employment, in the period 2018 - 2022. This research is Quantitative due to its nature, and Descriptive due to its level of explanation, with Non[1]experimental design. The conclusions derived from the research are that Micro Companies are the main generators of employment in Loreto throughout the period 2018 - 2022, employing 403,492 people on average, representing 77.70% of the employed population. On the other hand, the occupation category that provides the most work is Independent Worker, with 260,167 employees working as such on average, equivalent to 50.10% of employed people. Likewise, the main occupation carried out by employed people is Service Workers, Shop and Market Salespeople, where 112,168 individuals work on average, equal to 21.60% of the total. Finally, Agriculture and Fishing is the economic activity that brings together 29.70% of workers, equivalent to the amount of 154,231 people on average. In conclusion, Micro Companies are the ones that provide the most work and are Independent Workers.